Aetiology of acute diarrhoea in children in Shanghai, 2015–2018 - Chang, Hailing; Guo, Jiayin; Wei, Zhongqiu; Huang, Zheng; Wang, Chuning; Qiu, Yue; Xu, Xuebin; Zeng, Mei (PloS one, 2021)
Diarrhoea remains a major cause of childhood morbidity and mortality worldwide. This study aimed to monitor the aetiology of acute diarrhoea in children in Shanghai. Paediatric outpatients with acute diarrhoea were enrolled in the study from Jan 2015 to Dec 2018. Faecal samples were collected for testing. Enteric bacteria were identified and typed by culture and serotyping, respectively. Enteric viruses were identified by real-time PCR. Enteric pathogens were identified in 1572 (58.4%) of the 2692 enrolled children with acute diarrhoea. Viruses were detected more frequently than bacteria (41.3% versus 25.0%). Nontyphoidal Salmonella spp. (NTS) was the most common (10.3%) bacteria isolated, followed by enteropathogenic Escherichia coli (EPEC) (6.5%), enteroaggregative Escherichia coli (EAEC) (6.2%), Campylobacter spp. (3.6%), enterotoxigenic Escherichia coli (ETEC) (1.1%), Shigella spp. (0.2%), and enterohemorrhagic Escherichia coli (EHEC) (0.1%). Rotavirus was the most common (16.0%) virus detected, followed by norovirus (15.5%), adenovirus (7.2%), sapovirus (3.0%) and astrovirus (2.7%). Rotavirus, norovirus and NTS were the major pathogens responsible for diarrhoea in Shanghainese children. Improving uptake of the rotavirus vaccine and strengthening foodborne-pathogen prevention will aid in reducing the burden of diarrhoeal disease in children in Shanghai.